2016
DOI: 10.1108/ijsi-07-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of steel structures – a review of useful guidelines

Abstract: Purpose – Since the use of advanced finite element analysis (FEA) in the design of steel structures has been increasing its popularity in order to avoid unsafe or highly conservative designs, a solid know-how in computer-aided design (CAD) and engineering (CAE) codes is necessary. Therefore the purpose of this paper is to provide an extensive review of useful guidelines concerning modelling, simulation and result validation for the accurate performance of those analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Penggunaan logam berkekuatan tinggi dan/atau keuletan tinggi, seperti baja, paduan aluminium dan titanium, serta kemajuan teknologi manufaktur baru-baru ini, telah memungkinkan untuk membangun sistem/anggota struktural ramping yang sangat efisien (Abambres & Arruda, 2016). Salah satu metode yang digunakan untuk merancang kekuatan adalah dengan metode simulasi numerik elemen atau finite element analysis hingga (FEA) menggunakan software Solidworks Simulation.…”
Section: Pendahuluanunclassified
“…Penggunaan logam berkekuatan tinggi dan/atau keuletan tinggi, seperti baja, paduan aluminium dan titanium, serta kemajuan teknologi manufaktur baru-baru ini, telah memungkinkan untuk membangun sistem/anggota struktural ramping yang sangat efisien (Abambres & Arruda, 2016). Salah satu metode yang digunakan untuk merancang kekuatan adalah dengan metode simulasi numerik elemen atau finite element analysis hingga (FEA) menggunakan software Solidworks Simulation.…”
Section: Pendahuluanunclassified
“…In order to quantify the effects of butting on this single joint, this model was run for three geometric conditions: (i) butted tube profiles for the down tube (t = 0.8/0.5/0.8 mm); (ii) straight gauge tubes using the largest wall thickness (t = 0.8 mm, referred to as the maximum material condition, MMC); and (iii) straight gauge tubes using the smallest wall thickness (t = 0.5 mm, referred to as least material condition, LMC). Solid tetrahedral elements were used to account for the tapered butted profiles in the tubes and a mesh refinement was applied until the results converged within 98% of a target accuracy in the fillet area [25]. In the first instance, a 1 N in-plane bending force was applied to the end surfaces of the…”
Section: Model 1-finite Element Model Of a Single Jointmentioning
confidence: 99%
“…This model was used previously in [17], and was extended in this study to allow for tube butting profiles to be accounted for in the top tube, downtube and seat tube and again a mesh refinement was applied until the results converged within 98% of a target accuracy in the fillet area [25]. The frame material properties were the same as in 2.1 above, and the load cases were based on those presented in [2,3,17] for the in-plane bending due to a road bump at the front wheel, and out of plane/torsion due to climbing out of the saddle.…”
Section: Model 2-finite Element Model Of a Whole Frame Assemblymentioning
confidence: 99%
“…Their study concluded that reducing the laminate thickness and modulus, reducing the adhesive thickness, or increasing the bond length can increase the bond strength between the strengthening FRP laminates and steel beams. Previous studies by Zhou et al [15], Abambres and Arruda [28], and Ulger and Okeil [29] examined the effects of initial imperfection on the behavior of strengthened steel beams. They first executed the preliminary FE models to extract the Eigen buckling mode shapes, which were later impregnated into the preliminary FE models to impose initial imperfections in the final FE model.…”
Section: Introductionmentioning
confidence: 99%